(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
We evaluated the fruit ripeness state and the morphometric variability of Genipa americana seeds proceeding from 6 populations of the hot zone of the department of Quindio. There were collected 60 ripe fruits of which 600 seeds took to evaluate it’s morfometry. The study was conducted in the Biotechnology laboratory of Study and Research on Biodiversity and Biotechnology Center at the University of Quindio (CIBUQ). We evalued the organoleptic and morfometric characteristics in the fruits; besides the characters: Weight, length, width, thickness, relation length - width, volume and seeds form, following the methodology of Mora and Casas (2005) with some modifications, to analyze population-level morphometric changes. We calculated thecoefficient and variation factor and we realized an principal components analysis by means of the program Matlab (Version 7.0). We found that G. americana fruits present variation in size, weight and number of seeds; equally a high coefficient and variation factor in the seeds form, variance of 38% in the first principal component and high intrapopulation variability in size, weight and seeds lengthf. The specie fruits and seeds present higher measures to the reported. It is probable that genetic factors affect the size weight and seed forms; though the variation comes principally from environmental factors,which like wise influence the survival, the growth and there production.